Hamka’s daʿwah reform: Islamisation of self, education, and institution - Ibrahim, Haslina (IIUM Press, 2022)
Abdul Malik Karim Amrullah or HAMKA (1908-1981) was a prominent Malay scholar and also an icon of daʿwah Islamiyyah. Although his name and works are common to the Malays, his daʿwah orientation needs to be explored further in view of the lethargic conditions of present daʿwah movements in the Malay lands. Granted the title Pahlawan Nasional Indonesia, Hamka‘s thought epitomised the idealism of daʿwah reform, and his activism symbolises the institutional configuration of daʿwah. Hamka went beyond the rhetoric slogan of Islam as a way of life when he brought tangible solutions to the problems that happen in society. The core inventory to that tangible solution, in his opinion, should start with oneself i.e. Islamisation of self, before any meaningful daʿwah can be administered to the community and institutions. This article attempts to promote Hamka‘s daʿwah reform; a synergised intellectualism and activism that are missing from the contemporary da‘wah orientations and led to its adversary effect on public understanding and practice of Islam.